Alcohol consumption patterns across Europe and adherence to the European guidelines in coronary patients: findings from the ESC-EORP EUROASPIRE V survey. (25th November 2020) - Van De Luitgaarden, I; Schrieks, I; De Bacquer, D; Van Oort, S; Mirrakhimov, E; Pogosova, N; Davletov, K; Dolzhenko, M; Van Ballegooijen, A; Kotseva, K; Grobbee, D; Beulens, J
Abstract: Introduction: Alcohol consumption is an important risk factor for cardiovascular morbidity and mortality worldwide. The highest levels of alcohol consumption are observed in Europe, where alcohol as contributing cause of coronary heart disease (CHD) is also most significant. Purpose: To describe patterns of alcohol consumption across different European regions and adherence to the current drinking guidelines in coronary patients with a recent CHD. Methods: The EUROASPIRE V survey has been conducted in 2016–2017 at 131 centers in 27 European countries in 9, 018 patients with a recent CHD. Median alcohol consumption, as well as the proportions abstainers and excessive drinkers (i.e. >70 grams of alcohol per week for women and >140 grams per week for men, as recommended by the European guidelines on cardiovascular prevention), were calculated for each European region (Eastern, Southern, Northern and Western Europe). To assess adherence to guidelines, proportions of participants who were advised to reduce excessive alcohol consumption, as well as the participants who were incorrectly not advised were calculated per European region. Results: Mean age was 64 years (sd=9.5), 75% was male. Abstention rates were 51% in males and 74% in females, whereas excessive drinking was reported by 10% of the males (highest in Western Europe (18%) and lowest in Eastern Europe (5%)) and 6% of the females (also highest in Western Europe (12%) and lowest in Eastern Europe (1.4%)). Overall, 57% of the participants were advised to reduce alcohol consumption. In the total population, 3% was incorrectly not advised (Figure 1), but this percentage differed by region with 9% in Western Europe as compared to 1% in Eastern Europe. In regions where alcohol consumption was highest, participants were less often advised to reduce their consumption. Conclusion: In this EUROASPIRE V survey the majority of patients with a recent CHD adhere to the current drinking guidelines and only a fraction of the population was incorrectly not advised to reduce consumption. However, substantial heterogeneity exists between European regions. Funding Acknowledgement: Type of funding source: None